PENYAKIT ANTRAKNOSA CABAI OLEH Colletotrichum sp. DI LAHAN RAWA KALIMANTAN SELATAN - Mariana Mariana; Elly Liestiany; Fahmi Rizali Cholis; Nazwan Syahbani Hasbi (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2021)
[CHILLI ANTHRACNOSE DISEASE BY Colletotrichum sp. AT SWAMP LAND OF SOUTH KALIMANTAN PROVINCE].  Anthracnose is one of the major economic constraints for chili production worldwide. This disease is caused by the fungus Colletotrichum sp. The yield loss reaches 50% - 100% in the rainy season. In swamps, the incidence of this disease begins to increase. As the basis for the integrated control of anthracnose, it is necessary to record disease incidence and identify pathogens that attack conditions in swampsThe disease intensity survey was conducted in Hiyung chilli cultivation of Hiyung village lowland and the tidal swamplands of Marabahan district. The method is using Purposive Random Sampling approach. The Koch’s Postulates is used to determined the cause of the disease. Identification of pathogens that cause anthracnose is carried out in laboratories and greenhouses. Determination of obtained pathogen’s type is using literature references. The results of this study indicate that Hiyung chilli in the Hiyung village lowland shows a fairly high incidence of disease – i.e 43.78%, moreover, the result of Marabahan district tidal swamplands is 29.29%. Three Colletotrichum species were found, namely Colletotricum truncatum, C. gleosporiedes and C. acutatum.